2003
DOI: 10.1096/fj.02-1186fje
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPAR‐α in streptozotocin‐induced diabetes is essential for resistance against acetaminophen toxicity

Abstract: Diabetic (DB) mice exhibit significant resistance to hepatotoxicants. The role of peroxisome proliferator receptor (PPAR)-alpha activation in diabetes, in protection against lethal acetaminophen (APAP) challenge, was investigated. Upon treatment with APAP (600 mg/kg, i.p., a LD100 dose in wild-type [WT] non-DB mice), WT-DB mice showed only 30% mortality and 40% less liver injury as measured by alanine aminotransferase and histopathology. In contrast, diabetes in PPAR knockout (PPAR-alpha-/-) mice failed to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 57 publications
(91 reference statements)
3
43
0
Order By: Relevance
“…Studies in diabetic mice have demonstrated that increased PPAR-␣ activation provide protection against acute hepatotoxicity from acetaminophen as the result of increased hepatocyte proliferation in response to toxic challenge associated with upregulation of cyclin D 1 (43). This protection was abolished in diabetic PPAR-␣ knockout mice (43). A similar mechanism may underlie the increased hepatocyte proliferation observed with EtOH treatment in underfed rats in the present study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Studies in diabetic mice have demonstrated that increased PPAR-␣ activation provide protection against acute hepatotoxicity from acetaminophen as the result of increased hepatocyte proliferation in response to toxic challenge associated with upregulation of cyclin D 1 (43). This protection was abolished in diabetic PPAR-␣ knockout mice (43). A similar mechanism may underlie the increased hepatocyte proliferation observed with EtOH treatment in underfed rats in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…This suggests a positive role for PPAR-␣ in the regulation of hepatocyte proliferation. Studies in diabetic mice have demonstrated that increased PPAR-␣ activation provide protection against acute hepatotoxicity from acetaminophen as the result of increased hepatocyte proliferation in response to toxic challenge associated with upregulation of cyclin D 1 (43). This protection was abolished in diabetic PPAR-␣ knockout mice (43).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of CR diets on Hsps, inflammatory cascades and PPAR activity have been well documented (Nguyen et al, 1999;Yu and Chung, 2001;Shankar et al, 2003;Tsuchiya et al, 2005), and are consistent with the increased ability of these mice to resist xenobiotic insults. In dwarf mouse models, it has been shown that constitutive PPAR-α activity and its related gene products is increased (Stauber et al, 2005;Masternak et al, 2005), and that Ames dwarf mice exhibit an enhanced resistance to paraquat-induced lethality (Bartke et al, 2001a) while GHR-KO mice are relatively sensitive to paraquat-induced death (Hauck et al, 2002); however little else is known about xenobiotic metabolism in these mouse models.…”
Section: Discussionsupporting
confidence: 53%
“…The pathogenesis of liver cell death in response to acetaminophen (APAP) is multifaceted, and in addition to intrinsic hepatocyte responses to APAP metabolites, is influenced by proinflammatory cytokine cascades (Laskin and Laskin, 2001), heat shock proteins (Hsp) (Tolson et al, 2006), and peroxisome proliferator activated receptor (PPAR)-α activity (Nguyen et al, 1999;Shankar et al, 2003). The hepatic level of reduced glutathione is also an important factor in APAP-induced damage (Oz et al, 2005) and may contribute to some of the animal-to-animal variation in the response to APAP.…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast, type 1 DB mice challenged with TA and acetaminophen (APAP) exhibit higher hepatic tissue repair (Shankar et al, 2003a) and higher renal tissue repair after challenge with 1,2-dichlorovinyl-L-cysteine . It is known that hepatoprotection in type 1 DB mice is dependent on PPAR-␣ activation (Shankar et al, 2003b).…”
mentioning
confidence: 99%